Relevansi Film Animasi Riko The Series Season 3 Terhadap Pembentukan Akhlak Dengan Metode Pembiasaan - Novia Dwi Rahmawati; Ummi Nur Hidayah; Fadilah Nur Auliya; Arumaisah Arumaisah; Suci Indah Noviyana (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The era of globalization has helped shape the character of children through the types of shows that are often watched. Various shows resulted in the decline of morals in children. The purpose of this study is to analyze the relationship between the animated film Riko The Series on moral formation through the habituation method. This study uses a qualitative descriptive approach through the description of each episode in this animated film. The results of this study indicate that there is a relationship between the animated film Riko The Series and the formation of morals in the form of the habit of greeting, thanking, sorry and always saying tayyibah sentences. This animated film is expected to be a guide for parents to educate their children. Keywords: film Riko The Series; moral formation; relevance